2017
DOI: 10.1016/j.cropro.2016.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Weed management using crop competition in the United States: A review

Abstract: Exploiting the competitive ability of crops is essential to develop cost-effective and sustainable weed management practices. Reduced row spacing, increased seeding rates, and selection of competitive cultivars can potentially manage cropeweed competition in cotton, soybean, wheat, and corn. These cultural weed management practices facilitate a more rapid development of crop canopy that adversely affect the emergence, density, growth, biomass, and subsequently the seed production of weeds during a growing seas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 94 publications
3
71
0
2
Order By: Relevance
“…The definition of the critical period of interference prevention (CPIP) in wheat and other crops is an extremely important tool for the adoption of integrated weed management in order to avoid losses and unnecessary use of herbicides. Th erefore, the precise determination of this period is complex, because factors such as sowing time, crop population, nitrogen fertilization rates and time, weed species and populations present in the area, and edaphoclimatic characteristics can considerably infl uence the results in diff erent locations and years (Jha et al 2017).…”
Section: Interference Periodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The definition of the critical period of interference prevention (CPIP) in wheat and other crops is an extremely important tool for the adoption of integrated weed management in order to avoid losses and unnecessary use of herbicides. Th erefore, the precise determination of this period is complex, because factors such as sowing time, crop population, nitrogen fertilization rates and time, weed species and populations present in the area, and edaphoclimatic characteristics can considerably infl uence the results in diff erent locations and years (Jha et al 2017).…”
Section: Interference Periodsmentioning
confidence: 99%
“…The results showed that the cultivar TBIO Pioneiro presented maximum losses of more than 100% in all the explanatory variables, differently from the cultivar TBIO Alvorada, which presented the same development cycle and showed only a loss of more than 100% for the variable plant population (Table 1). This may be due to the initial growth difference, plant height, tiller production capacity and leaf size, which are directly associated with the yield potential of the species (Mason et al 2007;Jha et al 2017).…”
Section: Competitiveness and Economic Threshold Level (Etl) Between Wmentioning
confidence: 99%
“…Weeds reduce crop growth and yield by competing with field crops for environmental resources such as light, water, and nutrients . The cash crop yield reduction is increased when weed competition occurs in early growth stages.…”
Section: Introductionmentioning
confidence: 99%
“…Weeds reduce crop growth and yield by competing with field crops for environmental resources such as light, water, and nutrients. [1][2][3] The cash crop yield reduction is increased when weed competition occurs in early growth stages. Overall, weed infestation contributes to the largest potential yield losses (34%) relative to other plant pests such as insects or pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the yield per unit area and total production level in maize planting is an important way to ensure China's national food security [3] . In the world, weeding and plant protection has been an important stage in maize production, and product quality and yield are directly affected by working performances of weeding and plant protection machinery [4,5] . In the middle and late stages of maize planting, its growth and development is the most vigorous with frequent occurrence of pests, thus pest control in the middle and late periods determines the maize output.…”
Section: Introduction mentioning
confidence: 99%